To the question of reasonableness in tax relations - Pilipenka, Aleksandr A. (Journal of the Belarusian State University. Law, 2024)
The article examines the applications of the «reasonableness» category in tax relations. On the basis of the analysis, it was concluded that reasonable restraint was needed in the activities of officials of the supervisory authorities, especially in matters related to discretion in making appropriate decisions. The legal regulation of tax relations at the current stage of economic development of the Republic of Belarus should be based on reasonable restraint and reasonable prudence on the part of state authorities.